Community participation — a necessary element of community development projects - Khan, Zainu; Haupt, Theo (University of the Free State, 2006)
This article presents a number of important findings of a research project evaluating the importance of community participation in infrastructure delivery in the Western Cape. There is an emerging trend in South Africa that recognises that development is much more than the expansion of income and wealth and that economic growth is not enough. The focus is increasingly on human development. Participation in the development process must allow the members of the communities to use their own views and convictions to address specific conditions and problems prevailing in their community. In addition, participation must be acknowledged as a voluntary process that influences the direction and execution of community development projects in contrast to communities merely being consulted or receiving project benefits. The emerging participatory paradigm suggests two perspectives. The first consists of substantively involving local people in the selection, design, planning and implementation of programmes and projects that will affect them. The second is to make more continuous and comprehensive feedback an integral part of development activities. This paper reviews community participation and its importance in the delivery of development projects.

Hierdie artikel gee ‘n aantal belangrike bevindinge weer oor ‘n navorsingsprojek in die Wes-Kaap wat die belangrikheid van gemeenskapsdeelname in die lewering van infrastruktuur evalueer. Daar is ‘n opkomende neiging in Suid-Afrika wat erken dat ontwikkeling veel meer is as die uitbreiding van inkomste en rykdom en dat ekonomies groei nie genoeg is nie. Die fokus is al hoe meer op die ontwikkeling van mense. Deelname in die ontwikkelingsproses moet lede van die gemeenskap toelaat om hul eie oortuigings te gebruik om spesifieke probleme heersend in hul gemeenskap aan te spreek. Deelname moet erken word as ‘n vrywillig proses wat die rigting en uitvoering van gemeenskapsontwikkelingsprojekte kan beinvloed in teenstelling met gemeenskappe wat skaars geraadpleeg word of projekvoordele ontvang. Die opkomende deelnemende paradigma stel twee perspektiewe voor. Die eerste is dat plaaslik mense betrek word in die keuse, ontwerp, beplanning en implementasie van programme en projekte wat hulle sal affekteer. Die tweede is om voordurende verstaanbare terugvoering ‘n volledige deel van ontwikkelingsaktiwiteite te maak. Hierdie artikel gee ‘n oorsig oor die belangrikheid van gemeenskapsdeelname in die lewering van ontwikkelingsprojekte.
Keywords: Community participation; Community development; Development projects